The effects of climate and humic substances on disinfection performance in Arctic wastewater stabilization ponds - MacDougall, Alan (2017)
This thesis is an investigation of disinfection in wastewater stabilization ponds (WSPs) as it relates to adequate wastewater treatment and, ultimately source water protection (SWP) in northern, particularly Indigenous, communities. WSPs are considered sustainable utilitarian wastewater treatment technologies that are cost efficient and require minimal operation and maintenance. However, their performance is highly dependent on environmental conditions and disinfection performance, specifically, can be compromised in northern climates. The research is motivated by the following question: are there any simple approaches that could improve WSP disinfection without the need for conversion to a full-scale conventional treatment plant? The first study compared the ability of existing models in predicting cold climate disinfection performance in WSPs by comparing their predictions of mortality rates for fecal coliform bacteria with rates observed in a single-stage WSP in Pond Inlet, NU, during the 2015 treatment season. The results of this study demonstrated that existing models exhibit limitations in representing disinfection performance in Arctic WSPs. The second study focused on the development of a sunlight-mediated disinfection model for cold climate WSPs. A 2k factorial design was implemented to enable the examination of interaction effects of independent predictor variables related to sunlight-mediated disinfection (pH, dissolved oxygen, depth-averaged irradiance) on the mortality rates of Escherichia coli ATCC 11229. A controlled atmosphere chamber (CAC) was designed to control these parameters. Mortality rates between -0.8198-1.1057 h^-1 were observed throughout the experiments. A numerical model was presented and demonstrated a significant fit (p<0.001) to the data collected in the experiment. Temperature was found to have a more complex relationship with disinfection than previously thought, likely affecting both the growth and death rates of E. coli. In addition, the effect of humic substances (HS) ...